Isolated, well-defined organovanadium(iii) on silica: single-site catalyst for hydrogenation of alkenes and alkynes. Issue 53 (11th May 2017) - Sohn, H.; Camacho-Bunquin, J.; Langeslay, R. R.; Ignacio-de Leon, P. A.; Niklas, J.; Poluektov, O. G.; Liu, C.; Connell, J. G.; Yang, D.; Kropf, J.; Kim, H.; Stair, P. C.; et al.
Abstract : Well-defined, isolated, single-site organovanadium(iii ) catalyst on SiO2 for unprecedented liquid- and gas-phase hydrogenation of alkenes and alkynes under mild conditions. Abstract : A well-defined, isolated, single-site organovanadium(iii ) catalyst on SiO2 [(SiO2 )V(Mes)(THF)] was synthesized via surface organometallic chemistry, and fully characterized using a combination of analytical and spectroscopic techniques (EA, ICP, 1 H NMR, TGA-MS, EPR, XPS, DR-UV/Vis, UV-Raman, DRIFTS, XAS). The catalyst exhibits unprecedented reactivity in liquid- and gas-phase alkene/alkyne hydrogenation. Kinetic poisoning experiments revealed that 100% of the V sites are active for hydrogenation.